Harry S. Truman - Truman, Margaret, 1924- (New York, Morrow, 1973)
The astonishing story of Bess Truman and her love for her husband, Harry, as only their daughter could tell it. Bess Truman is more than a rare, intimate, and surprising portrait of a famous First Lady who kept her deepest feelings and considerable influence on President Truman hidden from public view. It also is the heartwarming story of an enduring love and a remarkable political partnership. Bess Wallace was born in 1885 in Independence, Missouri, into a secure world full of strong ideas. Young Bess was beautiful, popular, and strong-willed and could play third base and swim and ride as well as any boy. Harry Truman was a farmer's son to whom Bess always seemed out of reach. Their courtship was long and arduous, but Harry, as revealed through his endearing letters, was full of humor, gentleness, determination, and undying love that would win Bess over to him. And for sixty-nine years, Harry would be the center of her life
Keywords: Truman, Harry S., -- 1884-1972.; United States -- Politics and government -- 1945-1953.